The problems of applying criminal enforcement legislation in institutions of mixed security in the light of human rights concepts - Amanzholova, B.A. (Ye.A.Buketov Karaganda State University Publishing house, 2018)
Failure to observe of legal interests in regard to convict, confined, is severe violation of human rights, that often remains unnoticeable and unstudied. And it, in spite of fact, that researches of the UNO about violations of rights and freedoms in regard to convict, marked that celled and detained, being in establishments of the mixed safety, subject to the higher risk of failure to observe of their legal interests, what practically all other in other types of establishments of the criminally-executive system of Kazakhstan. It is very difficult to make the complete and clear picture of distribution of violations in regard to the people had in custody. Nevertheless, there are reliable and solvent proofs that this category of persons, being in a police and in establishments of the pre-trial having in custody, subject to the substantial risk of violation of human rights, both in the developed and in developing countries. Some types of violations in such establishments are widely widespread, and on occasion is considered a norm. The set patterns, taking into account the wide sphere of their use of, are not exhaustive and within the framework of one article does not allow to overcome all varied spectrum of pressing questions of practice, but can serve as an eloquent example that a Criminally-executive code yet needs some additions and changes.
Аралас қауіпсіздікті қамтамасыз ету мекемелерінде адам құқықтарын қорғау тұжырымдамалары аясында қылмыстық-атқару заңнамасын қолдану мəселелері
Проблемы применения уголовно-исполнительного законодательства в учреждениях смешанной безопасности в свете концепций прав человека
Keywords: conceptions of human rights; observance of human rights; rights and of freedom of convict; legal interests of detained; criminally-executive code; violations of human rights; detention facility; establishments of the criminally-executive system